Estimation of greenhouse gas emissions in rice based cropping systems under fertigation using cool farm tool - LATA, SUMAN; KOHLI, ANSHUMAN; SINGH, YANENDRA KUMAR; SHAMBHAVI, SHWETA; GHOSH, MAINAK; GUPTA, SANJEEV KUMAR (Journal of Soil and Water Conservation, 2020)
Greenhouse gas emissions were estimated using the Cool Farm Tool (CFT) model in four rice based cropping systems under three fertigation regimes during the fifth year of a zero till system. Fertilizer N management strategies had a strong effect on N2O emissions, that were higher in rice-barley and ricechickpea cropping systems due to higher inherent available soil nitrogen. Rice-durum wheat, ricechickpea, rice-lentil and rice-barley cropping systems showed susceptibility in decreasing order for incremental fertilizer N application. The safe levels of fertilizer N application up to which the nitrous oxide emissions can be avoided are 17.60, 6.60, 13.46 and 5.31 kg ha-1 in these cropping systems respectively. Nitrous oxide emission intensity decreased with decrease in fertilizer and irrigation intensity and followed the order rice-chickpea> rice-lentil> rice-durum wheat> rice-barley. With similar flooding across treatments, methane emissions were statistically similar under various fertigation regimes and cropping systems. In kharif and rabi seasons respectively, CO2 emissions were attributable to fertilizer use and the amount of irrigation water applied, respectively and followed the order W3>W2>W1. Across cropping systems, CO2 emissions were more in rice-durum wheat attributable to fertilizer production and use. Cumulative GHG emissions (kg CO2-eq) were maximum in W3 followed by W2 and minimum in W1. During kharif season, maximum GHG emissions were estimated in rice-lentil cropping system. During rabi season, the emissions were higher in rice-durum wheat cropping system followed by rice barley, rice-lentil and rice chickpea cropping systems due to higher rates of fertilizer application in the respective cropping systems